Analysis of patient data from laboratories during the Ebola virus disease outbreak in Liberia, April 2014 to March 2015. - Yuki Furuse; Mosoka Fallah; Hitoshi Oshitani; Ling Kituyi; Nuha Mahmoud; Emmanuel Musa; Alex Gasasira; Tolbert Nyenswah; Bernice Dahn; Luke Bawo (PLoS Neglected Tropical Diseases)
An outbreak of Ebola virus disease (EVD) in Liberia began in March 2014 and ended in January 2016. Epidemiological information on the EVD cases was collected and managed nationally; however, collection and management of the data were challenging at the time because surveillance and reporting systems malfunctioned during the outbreak. EVD diagnostic laboratories, however, were able to register basic demographic and clinical information of patients more systematically. Here we present data on 16,370 laboratory samples that were tested between April 4, 2014 and March 29, 2015. A total of 10,536 traceable individuals were identified, of whom 3,897 were confirmed cases (positive for Ebola virus RNA). There were significant differences in sex, age, and place of residence between confirmed and suspected cases that tested negative for Ebola virus RNA. Age (young children and the elderly) and place of residence (rural areas) were the risk factors for death due to the disease. The case fatality rate of confirmed cases decreased from 80% to 63% during the study period. These findings may help support future investigations and lead to a fuller understanding of the outbreak in Liberia.